Process evaluation of Emergency Department use of an Electronic Data Collection Tool that incorporates the International Classification of External Causes of Injury (ICECI) into the US National Burn Repository. (1st March 2011) - Villaveces, A; Peck, M; Price, G
Abstract : Context: The specific aim of our research was to evaluate the process of implementation of the International Classification of External Causes of Injury (ICECI) as an Emergency Department-based electronic surveillance tool for burn injuries for use in prevention activities and to reduce burn-related morbidity and mortality. Methods: We measured the ease, efficiency and accuracy of this tool when used by burn centres that are already engaged in gathering data for the National Burn Repository (NBR) of the American Burn Association. This version records data fields for all ICECI modules, and connects to NBR to pull data elements that will help select the correct ICECI codes, and produces reports on injury data. We measured quality variables including descriptions of registrar training, data entry dates, time required to complete each record and recorded problems experienced by registrars with data entry. Quality control was also maintained by having approximately one-in-ten charts reviewed by our prevention outreach clinician. Results: Our results indicate that over time data entry was conducted in less than 12 min for each record. We present results of this process evaluation based on data from six enrolled institutions. Conclusion: We have accomplished several goals including training of the registrar in the use of the tool, establishing a quality control mechanism for ensuring accuracy and reliability and incorporated ICECI data entry into the weekly routine of the burn registrar. Use of this tool is likely to improve data quality on burns and potentially other injuries.